Endocrown fracture resistance in molars using different CAD/CAM materials: a narrative review of invitro studies - Maita-Castañeda , Luis Mariano (2025)
Traditionally, the restoration of endodontically treated posterior teeth with significant coronal structure loss was done with a conventional crown and a core post. With advancements in adhesive techniques, alternative restorative approaches emerged, such as the endocrown, which utilizes the pulp chamber as a macromechanical retentive mean, thereby preserving the maximum amount of remaining dental tissue. Furthermore, a variety of CAD/CAM materials are now increasingly accessible to clinicians. The objective is to know the findings of in vitro studies on molars regarding the fracture resistance of endocrown using different CAD/CAM materials. This narrative review compiled original articles from bibliographic databases including PubMed, LILACS, SciELO, Scopus, and Google Scholar published between 2018 and 2023. It is concluded that lithium disilicate ceramic endocrown demonstrated the highest mean fracture resistance values compared to other groups, while repairable failure modes were observed in polymer-infiltrated ceramic-network (PICN) and resin-based composite materials.